Utilising problem-solving: from self-assessment to self regulating. Issue 3 (3rd July 2019) - Alzaid, Mohammed; Hsiao, Sharon
ABSTRACT: With the wide adoption of online platforms in education, having the content organised and readily available for the learners to self-assess their progress is crucial to ensure academic success. However, without the support of an active mentor, it might be difficult for the learners to guide themselves on how to accurately evaluate their learning outcome. This article focuses on how students benefited from self-assessing their programming course progress using an adaptive platform, namely QuizIT. We discuss the self-assessment procedure and development as it progresses into an open student model learning platform. The initial release was designated to assist programming novices as they encounter the programming learning journey. It was then followed by an extension to open the possibilities to the learner by having access to the learning model and gaining more control over the assessment experience. Quiz Adapt, was the set of features that provided an adaptive recommender based on an open learner model. The data collected from four study setups are evaluated to show the impact on the learning gain from interacting with the system. In addition, this paper sheds light on the effectiveness of daily learning opportunities in the introductory phase of education.